Developmental signaling: Does it bridge the gap between cilia dysfunction and renal cystogenesis?. Issue 2 (26th May 2014) - Tran, Pamela V.; Sharma, Madhulika; Li, Xiaogang; Calvet, James P.
<x xml:space="preserve">Abstract</x> For more than a decade, evidence has accumulated linking dysfunction of primary cilia to renal cystogenesis, yet molecular mechanisms remain undefined. The pathogenesis of renal cysts is complex, involving multiple cellular aberrations and signaling pathways. Adding to this complexity, primary cilia exhibit multiple roles in a context‐dependent manner. On renal epithelial cells, primary cilia act as mechanosensors and trigger extracellular Ca2+ influx in response to laminar fluid flow. During mammalian development, primary cilia mediate the Hedgehog (Hh), Wnt, and Notch pathways, which control cell proliferation and differentiation, and tissue morphogenesis. Further, experimental evidence suggests the developmental state of the kidney strongly influences renal cystic disease. Thus, we review evidence for regulation of Ca2+ and cAMP, key molecules in renal cystogenesis, at the primary cilium, the role of Hh, Wnt, and Notch signaling in renal cystic disease, and the interplay between these developmental pathways and Ca2+ signaling. Indeed if these developmental pathways influence renal cystogenesis, these may represent novel therapeutic targets that can be integrated into a combination therapy for renal cystic disease. Birth Defects Research (Part C) 102:159–173, 2014. © 2014 Wiley Periodicals, Inc.